Wilayatul Hisbah Communication in Enforcing Islamic Sharia Qanun regarding Jinayat Law through Islamic Education During the Covid 19 Pandemic in Lhokseumawe City - Said Mahdi; Syu Kholil; Sukiman Sukiman (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
As a special police force, Wilayatul Hisbah acts as a supervisory agency. This goal will be met if the community is well informed about the limitations of Shari'a Qanun violations. Public awareness will rise if they have a good and suitable understanding and information about Shari'a Qanun and other components of it, such as the penalty for transgressions, to induce fear and contemplation. Messages or information offered to the people of West Aceh in an attempt to avoid violations of Qanun Jinayat are focused on regional policies for Qanun Number 6 of 2014, with instructions including including community participation in efforts to implement Qanun Syariat, particularly Jinayat.This study will concentrate on Wilayatul Hisbah's da'wah communication strategy, particularly the pattern of Communication in Enforcing Islamic Sharia Qanun about Jinayat Law via Islamic Education During the COVID-19 Pandemic in Lhokseumawe City.In this study, the descriptive qualitative technique was used to collect data in the form of oral speech, writing, attitudes and behavior, as well as facts observed from the research subjects. To facilitate this data gathering, the authors employ the following data collection devices: 1. Interview Techniques 2. Observation Manual 3. Audio and video equipment.Wilayatul Hisbah West Aceh used the following da'wah communication strategies to prevent violators during the Pandemic Covid-19: Communicator Strategy (Wilayatul Hisbah communicators must be appealing and credible while speaking), Message Strategy (raising public legal knowledge), Media Strategy (using various types of activity and diverse communication media), and Effect Strategy (creating embarrassment in the perpetrators that makes you reluctant to do it again).